Comparison of two rotary systems in bacteria/lps removal from endodontic infections: randomized clinical trial - Camila Ambrósio Dias Machado; Amanda Caselato Andolfatto Souza; Caroline Loureiro; Frederico Canato Martinho; Luciano Tavares Ângelo Cintra; Eloi Dezan Junior; Rogério de Castilho Jacinto
Abstract: This clinical study compared the effectiveness of two rotary systems: HyFlex CM (Coltene-Whaledent, Altstetten, Switzerland) and ProTaper Next (Dentsply Sirona, Ballaigues, Switzerland) on the removal of cultivable bacteria and endotoxins from primarily infected root canals. This study was designed as a randomized single-blinded, 2-arm, clinical trial. Twenty-four primarily infected root canals were selected and randomly divided into 2 groups: HyFlex CM (n = 12); and ProTaper Next (n = 12). Samples were collected before and after the biomechanical preparation and inoculated in specific flasks. Irrigation was performed using 2.5% sodium hypochlorite. A kinetic turbidimetric lysate assay of limulus amoebocytes was used to quantify endotoxins. Microbiological culture technique was used to determine the count of bacterial colony forming units (CFU/mL). Data collected were statistically analyzed using SigmaPlot 12.0 for Windows. The Two-Way ANOVA statistical test was performed and the level of significance was 5%. In the samples before the biomechanical preparation, cultivable bacteria and endotoxins were evidenced in 100% of the cases. The culture analysis revealed that there was no statistically significant difference in the bacterial reduction between the two instrumentation systems. Endotoxins were present in 100% of the canals after instrumentation and there was no statistical difference between the two systems in endotoxin reduction. Thus, it was concluded that both instrumentation systems were effective in reducing root canal bacteria and endotoxins with primary endodontic infection and that there was no statistical difference between them. However, no system was able to eliminate 100% of the bacteria and their by-products.